The Influence of Corporate Governance Dimensions on Carbon Emission Disclosure: The Mediating Role of Financial Performance - Kiswanto, Kiswanto; Dalilati, Ufi; Hadi, Caraka; Hajawiyah, Ain; Harjanto, Atta Putra; Rahman, M. Fathur (International Journal of Energy Economics and Policy, 2026)
This study aims to investigate how corporate governance dimensions (board size, board nationality diversity, and institutional ownership affect carbon emission disclosure (CED) among publicly listed firms. Additionally, this research examines the mediating role of financial performance, measured by return on assets (ROA), in the relationship between corporate governance mechanisms and the level of carbon emission disclosure. The population of this study consists of energy sector companies that are listed on the IDX from 2020 to 2024. The analysis method used was panel data regression analysis with the help of Eviews-12 software. The results are expected to show that effective corporate governance, characterized by larger board size, higher nationality diversity, and greater institutional ownership-positively influences the extent of carbon emission disclosure. Financial performance (ROA) is anticipated to mediate this relationship partially, indicating that well-governed firms achieve superior profitability, which in turn enhances transparency in environmental reporting. This study integrates the corporate governance mechanism and financial performance pathway into a unified framework to explain firms’ carbon transparency behaviour. This research provides new empirical evidence from an emerging market context, highlighting how corporate governance dimensions drive voluntary carbon disclosure through financial outcomes. The study extends legitimacy and stakeholder theory by revealing that profitability serves as both a performance signal and a legitimacy tool in environmental communication. The findings contribute to global discourse on ESG integration and governance-driven sustainability disclosure.